2020
DOI: 10.1016/j.ajur.2020.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated AR and microRNA regulation in prostate cancer

Abstract: The androgen receptor (AR) remains a key driver of prostate cancer (PCa) progression, even in the advanced castrate-resistant stage, where testicular androgens are absent. It is therefore of critical importance to understand the molecular mechanisms governing its activity and regulation during prostate tumourigenesis. MicroRNAs (miRs) are small ∼22 nt non-coding RNAs that regulate target gene, often through association with 3′ untranslated regions (3′UTRs) of transcripts. They display dysregulation during canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 177 publications
(334 reference statements)
0
8
0
Order By: Relevance
“…Several variants, mutations, or even genomic rearrangements (TMPRSS2-ERG fusion is the most common in human prostate cancer, but is absent in small cell carcinoma of the bladder) are involved in pathophysiological situations correlated with AR signaling pathways; the complex interaction of each protein in a specific context may lead to different results, and represents a new pharmacological target for these pathologies, including bladder cancer [29]. New strategies that modulate AR signaling are developing, as demonstrated in the studies with long noncoding RNAs (lncRNAs), microRNAs, enhancer RNAs (eRNAs), and others [30][31][32][33]. The AR interacts with enzymes (cofactors) involved in the regulation of histone methylation, such as lysine-specific demethylase 1 (LSD1), KDM4B, KDM5B, KDM7A, EZH2, SMYD3 and PRMT5.…”
Section: Activation Of Androgen Receptor and Cofactorsmentioning
confidence: 99%
“…Several variants, mutations, or even genomic rearrangements (TMPRSS2-ERG fusion is the most common in human prostate cancer, but is absent in small cell carcinoma of the bladder) are involved in pathophysiological situations correlated with AR signaling pathways; the complex interaction of each protein in a specific context may lead to different results, and represents a new pharmacological target for these pathologies, including bladder cancer [29]. New strategies that modulate AR signaling are developing, as demonstrated in the studies with long noncoding RNAs (lncRNAs), microRNAs, enhancer RNAs (eRNAs), and others [30][31][32][33]. The AR interacts with enzymes (cofactors) involved in the regulation of histone methylation, such as lysine-specific demethylase 1 (LSD1), KDM4B, KDM5B, KDM7A, EZH2, SMYD3 and PRMT5.…”
Section: Activation Of Androgen Receptor and Cofactorsmentioning
confidence: 99%
“…These results indicate that miRNA-34a could be further targeted for drug resistance therapeutic purposes in hormone-resistant prostate cancer. In prostate cancer, miRNAs are reported to be modulators of androgen deprivation therapy (ADT) resistance [ 109 ]. Sun et al, (2012) [ 110 ] have reported that miRNA-221/222 are upregulated while miRNA-23b and miRNA-27b are downregulated in about 90% of metastatic castrate-resistant prostate cancer (mCRPC) cases compared with primary tumors.…”
Section: Mirna and Alternative Splicing-induced Drug Resistancementioning
confidence: 99%
“…Because of the high expression level and stability of circRNA, it is used as a competitive endogenous RNA (ceRNA) 6 . circRNA competes with miRNA to prevent the posttranslational inhibition of miRNA and target coding RNA, ultimately regulating the expression levels of target genes 7 .…”
Section: Introductionmentioning
confidence: 99%